Presence of the Primitive at the 9th Bienal de São Paulo - Emerson Dionisio de Oliveira (OBOE, 2023)
The presence of so-called “primitive” or “innocent” artists at the 9th Bienal de São Paulo (1967), within the vocabulary of popular art, was marked by frank and open public debate between the selection jury of the event and the critics of the time. This article seeks to present this debate, which is focused on the distinction between experimental art, new contemporary values, and production with a popular foundation. At stake was the presence and maintenance of certain senses of ancestry and national identity, strongly encouraged during the civil-military dictatorship and perceptible in the following Biennials, especially with the creation of the national Biennials at the end of the decade. The controversy revived the brief polemics, from two years earlier, surrounding the nomination of primitive artists to represent Brazil at the 1966 Venice Biennale and is here aligned with the dispute over contemporaneity in the production of Brazilian visual arts at the end of the 20th century.